Case report: Unruptured tubal pregnancy in the second trimester - Mame Diarra Ndiaye Guèye; Mamour Guèye; Ibou Thiam; Magatte Mbaye; Abdou Magib Gaye; Abdoul Aziz Diouf; Mouhamadou Mansour Niang; Jean Charles Moreau (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2013)
The incidence of ectopic pregnancies varies from 10 to 39.5/1,000 deliveries [1,2,3]. The ampullary portion of the fallopian tube is the most common location [4]. Many risk factors are associated with ectopic pregnancies. Tubal pregnancies generally rupture between 5 and 11 weeks of gestation